Enzymatic diagnosis of homocystinuria by determination of cystathionine-ß-synthase activity in plasma using LC-MS/MS - Alcaide, P; Krijt, J; Ruiz-Sala, P; Ješina, P; Ugarte, M; Kožich, V; Merinero, B (Clinica chimica acta; international journal of clinical chemistry, 2015)
BACKGROUND: Cystathionine β-synthase (CBS) is released into plasma from organs expressing this enzyme. Decreased plasma CBS activity has been demonstrated in CBS-deficient patients with 16 different genotypes. The aim of this study was to determine plasma CBS activity in patients carrying 11 additional genotypes using two LC-MS/MS methods. Patients and methods CBS activity was measured in EDTA or heparin plasma using either a previously described or a newly developed LC-MS/MS method optimized for analysis of the reaction product, 3,3-(2)H2-cystathionine, as its butyl ester derivative. We analyzed plasma samples from 26 CBS-deficient patients with known genotypes and 57 controls. RESULTS: We developed a new LC-MS/MS method for simple and sensitive determination of CBS activity. Plasma CBS activity was low (i.e., 0.001-0.036 of the multiples of median control values, MoM) in patients homozygous for the prevalent Hispanic mutation c.572C>T (p.T191M) but was highly elevated (2.95 MoM) in a single patient homozygous for the c.1330G>A (p.D444N) mutation. Patients with the remaining nine genotypes exhibited decreased activities (0.00-0.22 MoM), which did not overlap with the controls (0.29-2.10 MoM). CONCLUSIONS: The determination of CBS activity in plasma is a rapid and non-invasive procedure for detecting a subgroup of CBS-deficient patients with distinct genotypes.
Keywords: senioři; Pyridoxine response; Homozygote; Homocystinuria; genotyp; homocystinurie; kojenec; Genotype; cystathionin-beta-synthasa; mladiství; Cystathionine ß-synthase activity; LC-MS/MS; Middle Aged; mužské pohlaví; rodokmen; Pedigree; mutace; Infant; Adult; dítě; Cystathionine; Child; Child, Preschool; ženské pohlaví; Gene Expression; Mutation; Humans; předškolní dítě; Tandem Mass Spectrometry; chromatografie kapalinová; lidé středního věku; homozygot; Cystathionine beta-Synthase; exprese genu; tandemová hmotnostní spektrometrie; dospělí; Chromatography, Liquid; Female; Aged; Adolescent; cystathionin; lidé; Male